Theoretical Strength of Solids - Pokluda, Jaroslav (Communications - Scientific letters of the University of Zilina, 2004)
The significance of theoretical strength (TS) investigations is explained and a brief overview of the current state of TS calculations is presented on the background of a historical evolution. Influence of crystal defects on TS is outlined by taking into account published theoretical models. The study is completed by a discussion concerning differences between theoretical and experimental results.